A case of two traumatic penetrations of a duodenal diverticulum caused by a kick to the upper abdomen. (October 2021) - Shiraishi, Toshio; Wada, Hideo; Hashimoto, Shintaro; Katayama, Hiroki; Taba, Mitsuru; To, Kazuo
Abstract: Introduction and importance: A duodenal diverticulum is a pseudodiverticulum that lacks a proper muscular layer. Cases of traumatic penetration or perforation of a duodenal diverticulum are relatively rare. Case presentation: A 67-year-old woman was injured when her roommate kicked her in the upper abdomen, and was transferred to our hospital 6 h after the injury with upper abdominal pain and lethargy. Computed tomography revealed a duodenal diverticulum and retroperitoneal emphysematous changes and exudates. Peritonitis due to duodenal penetration was suspected and emergency laparotomy was performed. Intraoperative findings revealed two traumatic penetrations of the duodenal diverticulum. We resected the diverticulum with an automatic suture device and covered the resection site with omentum. Twenty-one days postoperatively, she was transferred to her original hospital with no complications following an uneventful postoperative course. Clinical discussion: Most causes of penetration or perforation of the duodenal diverticulum are diverticulitis, and few reports have described penetration or perforation of duodenal diverticulum due to trauma. Our case was extremely rare that caused by a kick to the upper abdomen and resulted in two penetrations of a duodenal diverticulum although factors contributing to the multiple penetrations were considered. Conclusion: Penetration or perforation of a duodenal diverticulum occasionally results in a rapid deterioration to a severe state. Comprehensive judgement of the general condition and laboratory findings and selection of an appropriate treatment policy is important. Highlights: Few reports have described penetration or perforation of a duodenal diverticulum due to trauma. This case is extremely rare of two penetrations of a duodenal diverticulum caused by a kick to the upper abdomen. Penetration or perforation of a duodenal diverticulum often leads rapidly to a severe state. Comprehensive judgement of the general condition and selection of an appropriate treatment policy is important.